(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The world seen rapid developments in the field of information technology within all life fields, particularly the educational field. Usually, we find the traditional educational methods lack a sense of realism and interaction. Solving this problem is by utilizing virtual reality technology to make actual practice present in the classroom. As an interactive technology, it provides students with an accessible, reliable environment that was previously unavailable and offered an opportunity for learning by practicing instead of teacher-centered learning and within a vision that does not look at the past but looks to the future. Virtual reality technology will change the nature of the relationship between the teacher and the student. Thus, the change will reach the nature of the educational spaces that contain this technology, which will significantly impact the design of school buildings and classes of the electronic future. With this, the research problem identified as an existing weakness in the directed knowledge base at the extent of the impact of virtual reality technology on the architectural design of the Iraqi educational spaces specifically Accordingly, the research sought to achieve its objectives by exploring the importance of virtual reality technology in the educational field and the essential technological components necessary to create virtual data, clarifying the difference between traditional education and modern education (technology-based) and by defining the status of conventional education in Iraq and Problems related to the low quality of the existing school buildings, and designing a classroom model that achieves virtual reality systems and at the same time is used for traditional lessons Building a theoretical framework to achieve these goals by extracting indicators that apply to the practical side is the plane to accomplish these goals. The framework includes attempts to prove the research hypothesis represented by the positive impact of virtual reality technology on the design of Iraqi educational spaces. Finally, the research results indicated that virtual reality technology has dramatically affected the future design of educational spaces. Adopting this technology in the educational process allowed students to develop their creativity, increase their motivation and gain real experience in a more interactive educational method.